To solve this system of equations, we can use the method of substitution or elimination.
Let's use the method of elimination to solve this system.
1. Multiply the second equation by 6 so that the coefficient of y in both equations is the same:
6(3x + y = -7)
18x + 6y = -42
2. Now, we have the equations:
3x + 6y = 18
18x + 6y = -42
3. Subtract the first equation from the second equation to eliminate y:
18x + 6y - 3x - 6y = -42 - 18
15x = -60
x = -4
4. Now, substitute x = -4 back into the second equation to solve for y:
3(-4) + y = -7
-12 + y = -7
y = -7 + 12
y = 5
Therefore, the solution to the system of equations is x = -4 and y = 5.
3x+6y=18
3x+y=-7
1 answer